2011
DOI: 10.1161/circresaha.110.234278
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Valvular and Vascular Sclerosis by Osteogenic Morphogens

Abstract: Vascular calcification increasingly afflicts our aging, dysmetabolic population. Once considered only a passive process of dead and dying cells, vascular calcification has now emerged as a highly regulated form of biomineralization organized by collagenous and elastin extracellular matrices. During skeletal bone formation, paracrine epithelial-mesenchymal and endothelial-mesenchymal interactions control osteochondrocytic differentiation of multipotent mesenchymal progenitor cells. These paracrine osteogenic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
201
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(212 citation statements)
references
References 180 publications
4
201
0
1
Order By: Relevance
“…Other data indicate that the occurrence of ectopic medial calcifications is associated with adventitious cells [17]. Vessel and valve endothelial cells serve as a cellular barrier between the blood and the main tissue components, but participate in the endothelial-mesenchymal transition, playing a key role in tissue fibrosis and calcification [18]. In vitro and ex vivo studies have established the involvement of inflammation in the calcification of both valves and vessels [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Other data indicate that the occurrence of ectopic medial calcifications is associated with adventitious cells [17]. Vessel and valve endothelial cells serve as a cellular barrier between the blood and the main tissue components, but participate in the endothelial-mesenchymal transition, playing a key role in tissue fibrosis and calcification [18]. In vitro and ex vivo studies have established the involvement of inflammation in the calcification of both valves and vessels [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…PKA, BMP, ERK, and Notch pathways and inflammatory cytokine signaling have been linked to VC induced by elevated phosphate or by diabetic milieu (22,36,39,40), whereas ␤-catenin activity is critical in warfarin-induced VSMC mineralization (18) and has been implicated in both diabetic calcification (41) and calcification of the heart valves (42). Based on the perceived mechanistic similarity between pathological and physiological calcification, C/EBP, JNK, and pRb pathways associated with osteogenesis (43-45) may also contribute to vascular mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated in animal models that VC may be induced by stimulating various genes, including bone morphogenetic protein (BMP)2, BMP4 (2,3), runt-related transcription factor (RUNX)2 and alkaline phosphatase (ALP) (4). Previous studies have revealed that BMP2 and BMP4, members of the transforming growth factor-b cytokine superfamily, participate in vascular calcification (5). Vascular endothelial and smooth muscle are key sources of BMPs, which when detected in calcified blood vessels may be associated with enhanced vascular calcification (6).…”
Section: Introductionmentioning
confidence: 99%